Analisis Yuridis Pemenuhan Hak Dasar Guru Honorer di SD Kasatriyan Surakarta - Nur Intan Zahrotul Muhtar; Asianto Nugroho; Sapto Hermawan (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This study is motivated by the importance of fulfilling the basic rights of honorary teachers as part of efforts to improve the quality of national education. Honorary teachers in private schools, particularly at SD Kasatriyan Surakarta, often face challenges related to welfare and legal protection that are not yet optimal. The study aims to analyze the conformity of the fulfillment of basic rights of honorary teachers at SD Kasatriyan Surakarta with the provisions of Law Number 14 of 2005 concerning Teachers and Lecturers. The research employs normative juridical and empirical juridical methods, with secondary data obtained from literature review and primary data collected through interviews and direct observations at the research site. The findings indicate that most honorary teachers receive salaries far below the Surakarta City Minimum Wage and lack social welfare guarantees, such as health insurance or accident protection. Furthermore, access to training, competency development, as well as recognition and promotion, remains very limited. These findings highlight a gap between legal norms and field practices, necessitating more serious policy interventions from the government and foundations to ensure the rights of honorary teachers are fully met and to enhance the overall quality of education.